Perancangan Pembatas Ruang (Territory) Multifungsi untuk Menunjang Kenyamanan Pengguna di Area Tunggu Ruang Publik - Syahputri, Marwah Annie; Andrianto, Andrianto; Ramawisari, Ica (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Cafe business players currently continue to develop their services according to community needs and continue to strive to align their business development, which of course cannot be separated from technological developments. This development is facilitated by the existence of online transportation applications where there are online food delivery services. The Chatime Buah Batu Square waiting area is provided for visitors who eat on site or take away and also for online motorbike taxis in the same area and the space is limited, thereby reducing the comfort of visitors and online motorbike taxis because they feel uncomfortable and disturbed at certain peak times and hours such as lunch time, afternoon or after work around 4-5 pm, and dinner time. The research method in this study is a qualitative method in the form of observation, interviews, questionnaires, and literature studies through journals and other literature sources. The design method used is the User Centered Design UCD method by carrying out the design process from the data obtained in the form of ideation, sketching, 3D design, prototyping, testing and finishing. Designing multifunctional partitions with waiting chairs can increase comfort for main visitors and online motorcycle taxis with visuals that match the cafe concept and can be placed in limited areas.